VISUAL LITERACY FROM THEORY TO PRACTICE: A PARADIGM OF VISUAL THINKING, LEARNING AND COMMUNICATION: การรู้เชิงทัศนะจากทฤษฎีสู่การปฏิบัติ: กระบวนทัศน์ในการคิด การเรียนรู้ และการสื่อสารด้วยภาพ - Wetcho, Suthanit; Na-Songkhla, Jaitip (Journal of Education and Innovation, 2020)
In the digital age, data is quickly shared through online digital devices. Sending messages using visuals is therefore one of the communication methods between senders and receivers to quickly create understanding and effectively communicate the intention of the sender. Developing the ability to understand and use images, including the ability to think, learn, and express themselves in visual form is also known as "Visual Literacy". It is important for those who want to receive and send messages efficiently. The development process may occur from three important components: "visual thinking", "visual learning" and "visual communication” as key components to the encoding and decoding of messages including sending visual messages through various media and channels. This article will explain the theory of three important components which leads to the application and practice in the learning design and to use in daily life.